An evaluation of the interaction of place and community-based participatory research as a research methodology in the implementation of a sexually transmitted infection intervention for Greenlandic youth - Rink, Elizabeth (Int J Circumpolar Health, 2016)
Newly emerging research suggests that the actual physical location of a study and the geographic context in which a study is implemented influences the types of research methods most appropriate to use in a study as well as the study's research outcomes. This article presents a reflection on the extent to which place influenced the use of community-based participatory research (CBPR) as a research methodology in the implementation of an intervention to address sexually transmitted infections in Greenland. An evaluation of the interaction between place and CBPR suggests that the physicality of place influenced the intervention's successes and challenges. Future research that uses CBPR as a research methodology in sexual and reproductive health research in the Arctic warrants situating the research design, implementation and outcomes within the context of place.